Redox Signaling in Endosomes Using the Example of EGF Receptors: A Graphical Review - Dana Maureen Hebchen; Katrin Schröder (MDPI AG, 2024)
Early endosomes represent first-line sorting compartments or even organelles for internalized molecules. They enable the transport of molecules or ligands to other compartments of the cell, such as lysosomes, for degradation or recycle them back to the membrane by various mechanisms. Moreover, early endosomes function as signaling and scaffolding platforms to initiate or prolong distinct signaling pathways. Accordingly, early endosomes have to be recognized as either part of a degradation or recycling pathway. The physical proximity of many ligand-binding receptors with other membrane-bound proteins or complexes such as NADPH oxidases may result in an interaction of second messengers, like reactive oxygen species (ROS) and early endosomes, that promote the correct recognition of individual early endosomes. In fact, redoxosomes comprise an endosomal subsection of signaling endosomes. One example of such potential interaction is epidermal growth factor receptor (EGFR) signaling. Here we summarize recent findings on EGFR signaling as a well-studied example for receptor trafficking and trans-activation and illustrate the interplay between cellular and endosomal ROS.